ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN AKUNTANSI AKRUAL PADA PEMERINTAH DAERAH KABUPATEN BANTUL - Jayanti Mandasari; Zulkifli Zulkifli (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2018)
The purposes of this study are : 1. to analyze the influence between the education level of financial staff on the application of accrual accounting. 2. to analyze the effect of the experience of running the cash basis toward accruals on the accrual accounting application. This research design is quantitative research by using regression test, where the principal data from samples of a population is collected by distributing questionnaire instrument. Hypothesis testing performed by Multiple Linear Regression was used to test the effect between variables of education staff finance level (X1) and experience running cash basis toward Accrual (X2) on Accrual Accounting (Y) application. The results of this study indicate that: a) The level of education of financial staff (X1) has a positive influence on the application of accrual accounting (Y). This is indicated by the results of research showing that staff education level has an explanation power of 59.3%. b) The result of experience analysis running cash basis toward accrual (X2) show value t count equal to 4,744 with sig. 0,000. Therefore the value of sig. less than0.05 then Ho is rejected, which means experience running the cash basis (X2) has a positive effect on the application of accrual accounting (Y).